The thought of divergence: The concept of theology in Walter Benjamin - Silva Montellanos, Leonel Patricio (2017)
This text is a reflection about the theological conceptions of the German-Jewish philosopher Walter Benjamín. We argue that such theories condition their conception of the world and that the Messianic materialist author's approach is the clearest example of the possibility of a connection between monotheistic religiosity and critical-libertarian thinking. If, over the years, he has been considered as a "heterodox" author derived from the Frankfurt School, it is questionable whether his living interpretation of Marxism, given its marginal Jewish in Europe between the wars, is no more authentic than purely speculative interpretations that precisely by dispensing with the social factor, they remove Marxism, the main feature of its materialism: being a doctrine experienced in its own flesh by who theorizes and not be only an abstract form, devoid of real and concrete foundation. In times like these (21st century) and in places like this (Latin America) we must ask ourselves how effective is a critical discourse arising from marginality, precariousness and despair in the presence of death and abomination. Reflecting from pain, one has a full understanding of that which should not be repeated and thinking from injustice can understand the need for redemption and liberation.